Religious Voting and the Gender Gap: Support for the Radical Right in Chile - Perez-Cosgaya, T (Scandinavian University Press, 2024)
Research Question: What explains support for radical-right candidates and to what extent are voters’ gender, income and religion good predictors of that support? Context: This article answers such questions using the case of Chile, specifically the 2021 presidential election, in which a candidate from the radical right, José Antonio Kast, reached the election’s second round. Method: Based on opinion polls and electoral data aggregated at the municipality level, a series of multivariate statistical models was developed to explain the vote for Kast. Conclusions: The following three findings were obtained. First, there was a significant gender gap, with greater support from men than women. Second, this gender gap is highly dependent on the socioeconomic conditions of voters, with the support of men from higher-income segments of the population being more favourable to the radical right. The third is the radical right’s robust backing from the evangelical population. © 2024 Scandinavian University Press. All rights reserved.